Dari Eden ke Perjanjian Baru: Alkitab Menjawab Mengapa Saya Menikah - Sulistiono (Jurnal Teologi Trinity, 2025)
This article aims to explain the theological reasons why humans marry, as set out in the biblical narratives from Genesis to the New Testament. Through a review of literature and a theological interpretive approach, it demonstrates that marriage is an integral part of the divine mandate and a reflection of God's love, rather than merely a social or biological necessity. It highlights that marriage is rooted in creation, love, character development and participation in God's mission on earth. Furthermore, it discusses key principles for building a Christian family, including the roles of husband and wife, effective communication, financial management, and spiritual development. The article concludes that a healthy Christian marriage can only be established on the true principles of God's word.